Peran Kesenjangan Ekonomi terhadap Kejadian Kegemukan - Sari, Kencana; Indirawati, Lely; Utami, Nurhandayani; Amaliah, Nurillah (Media Penelitian dan Pengembangan Kesehatan, 2016)
Economic inequality relationship to health has been widely analyzed in western countries but is stilllimited in developing countries. Knowing the role of economic inequality against obesity is expectedto help overcome the problem of obesity in Indonesia. This study aims to analyses the relationshipof economic inequality and obesity. The data were obtained from a cross-sectional Indonesian BasicHealth Research (Riskesdas) year 2010. The subjects consisted of 125563 respondentâs ages 19-55years old that derived from 251388 household members nested within 69300 households nested within 2798 communities nested within 33 regions. Obese was categorized as body mass index more than 25.Community level exposures included economic inequality that based on Gini coefficient. The data were analyzed with multilevel logistic regression. The prevalence of obesity in Indonesia was 22.96 percent.The economic inequality was ranged from 0.18-0.69 across 33 provinces in Indonesia. The economicinequality has a role on obesity although the role of the individual and household level on obesity isgreater (76.8%) compared to the role of economic inequality at the provincial level (23.2%). At theindividual level, variables that contribute to obesity were female (OR = 1.91), education > SMA (OR =1.18), married (OR = 2.70), and higher socioeconomic status (OR5th kuintil= 2 , 76). At the provincial level, economic inequalities increase the chances of obesity of 1.31 times. The higher the economic inequality in the province level is likely to increase the incidence of obesity but the effect was smaller than at the individual level factors. Obesity prevention are needed focusing on female, married, and higher socioeconomic status.Keywords:Â inequality, economic, obesityÂ AbstrakKesenjangan ekonomi telah banyak dianalisis di negara-negara barat tetapi masih terbatas di negara-negara berkembang. Mengetahui peran kesenjangan ekonomi terhadap kegemukan diharapkan dapat membantu mengatasi masalah kegemukan di Indonesia. Analisis ini bertujuan untuk mengetahui hubungan kesenjangan ekonomi dengan kegemukan. Analisis menggunakan data Riset Kesehatan Dasar (Riskesdas) tahun 2010 yang bersifat potong lintang. Subyek terdiri dari 125.563 responden berumur 19â55 tahun yang berasal dari 251.388 anggota rumah tangga dari 69.300 rumah tangga pada 2.798 blok sensus di 33 provinsi. Kegemukan dikategorikan sebagai indeks massa tubuh lebih dari 25. Eksposur di tingkat masyarakat yaitu kesenjangan ekonomi didasarkan pada koefisien Gini. Data dianalisis dengan multilevel regresi logistik. Prevalensi kegemukan di Indonesia adalah 22,96%. Kesenjangan ekonomi berkisar antara 0.18â0.69 di 33 provinsi di Indonesia. Kesenjangan ekonomi mempunyai peran terhadap kejadian kegemukan di tingkat individu dan rumah tangga. Namun, peran tingkat individu dan rumah tangga lebih besar (76,8%) dibandingkan peran kesenjangan ekonomi di tingkat provinsi (23,2%) terhadap kejadian kegemukan.Pada tingkat individu yang berperan pada kegemukan adalah jenis kelamin perempuan (OR=1,91), pendidikan > SMA (OR=1,18), kawin (OR=2,70), dan status sosial ekonomi semakin tinggi (OR kuintil 5=2,76). Pada tingkat provinsi, kesenjangan ekonomi meningkatkan peluang kegemukan 1,31 kali. Kesenjangan ekonomi semakin tinggi berpeluang meningkatkan kejadian kegemukan tetapi pengaruhnya lebih kecil dibanding faktor di tingkat individu. Pencegahan kegemukan yang berfokus pada individu yang berjenis kelamin perempuan, kawin, dan status sosial ekonomi semakin tinggiABSTRAKKata Kunci:Â kesenjangan, ekonomi, kegemukan